2023
DOI: 10.3390/robotics12030080
|View full text |Cite
|
Sign up to set email alerts
|

Variable Damping Actuator Using an Electromagnetic Brake for Impedance Modulation in Physical Human–Robot Interaction

Zahid Ullah,
Ronnapee Chaichaowarat,
Witaya Wannasuphoprasit

Abstract: Compliance actuation systems are efficient and safe, drawing attention to their development. However, compliance has caused bandwidth loss, instability, and mechanical vibration in robotic systems. Variable physical damping was introduced to address these issues. This paper presents a technique for obtaining variable damping properties using an electromagnetic brake. The relationship mapping of the voltage and the braking torque is studied and applied to the variable damping concept. A new model is proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In comparison to existing variable damping actuators based on friction [26], magnetorheological, and electrorheological principles [34][35][36], the PSDA proposed in this paper utilizes orifice effect to achieve damping adjustment, avoiding the continuous consumption of energy to maintain damping. While there were variable damping actuators using orifice effect [40], our PSDA embeds the variable damping mechanism within the rotating shaft of the actuator, making it more compact and suitable for robotic applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to existing variable damping actuators based on friction [26], magnetorheological, and electrorheological principles [34][35][36], the PSDA proposed in this paper utilizes orifice effect to achieve damping adjustment, avoiding the continuous consumption of energy to maintain damping. While there were variable damping actuators using orifice effect [40], our PSDA embeds the variable damping mechanism within the rotating shaft of the actuator, making it more compact and suitable for robotic applications.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there have been several methods used to achieve variable damping. Magnetorheological and electrorheological fluid-based dampers [34][35][36] were adopted in automotive and civil engineering applications. However, they need to continuously apply magnetic field or current to maintain the physical damping, which will consume a lot of energy.…”
Section: The Variable Damping Mechanismmentioning
confidence: 99%
“…This implies that K(θ 1 − θ e ) = τ ext for the shoulder and K(θ 2 − θ e ) = τ ext for the elbow. Consider the joint model in Equation (7), i.e., for the shoulder, as a second-order system represented as follows:…”
Section: Interaction Joint Torque Estimationmentioning
confidence: 99%
“…However, with developments in neuroengineering research, rehabilitation robots can be used to replace human physiotherapists, as shown in Figure 1b. Safe close-proximity human [1,2] and exoskeleton [3,4] interactions with robots can be achieved through two complementary strategies: (1) using smart actuators [5] with adjustable intrinsic properties, e.g., stiffness [6] and damping [7], and (2) by impedance control [8,9]. Impedance control provides safe and stable robotenvironment interaction.…”
Section: Introductionmentioning
confidence: 99%
“…An essential part of the research was also recently dedicated to passive systems [35][36][37][38] that are intrinsically safer, from the point of view of possible malfunctions, but which do not perform as well as the active ones. Interacting with the external environment is an essential aspect of controlling these devices [39][40][41][42][43]. In movements interacting with the environment, the interaction forces must be supported rather than opposed.…”
Section: Introductionmentioning
confidence: 99%